Bimaxillary jaw involvement in pediatric Burkitt lymphoma: A rare case with radiologic–histopathologic–immunohistochemical correlation - Joshi, Mruga; Parikh, Shilpa; Suthar, Prakruti; Shah, Jigna (Indian Journal of Case Reports, 2026)
Burkitt lymphoma (BL) is an aggressive B-cell non-Hodgkin lymphoma characterized by rapid proliferation and high chemosensitivity. Bilateral jaw involvement in sporadic BL is rare and may pose a diagnostic challenge. Here, we report the case of a 12-year-old male who presented with rapidly progressive bilateral facial swelling following dental trauma and extraction, with onset noted within 2 days post-extraction. Clinical and radiographic findings revealed diffuse gingival enlargement, loss of lamina dura, and displacement of developing teeth. Histopathological examination demonstrated a characteristic “starry-sky” appearance, while immunohistochemistry confirmed CD20+, CD10+, and LCA+ B-cell lineage with a Ki-67 index approaching 100%. The patient was treated with multi-agent COPADM chemotherapy and showed marked regression within 1 month. Early recognition of atypical oral swellings, especially those with rapid onset following dental procedures, and prompt biopsy are critical for timely diagnosis and effective management of this aggressive yet highly curable malignancy.